Basic Information of the Journal - Journal of Productive Discourse (Journal of Productive Discourse, 2025)
The Journal of Productive Discourse (ProD) is an international, not for profit, blind peer-reviewed journal of critical readings across disciplines. It aims to provide teachers, students and learned members of the community an authentic open-access platform featuring scholarly research, reviews and perspectives on the state of current discourse on topics of interdisciplinary interest. The annual journal is published both in print and electronic forms once a year on the 3rd of the month of Jestha in the Nepali calendar.